KETAHANAN BEBERAPA VARIETAS CABAI TERHADAP CUCUMBER MOSAIC VIRUS (CMV) (RESISTANCE OF SEVERAL CHILI VARIETIES ON CUCUMBER MOSAIC VIRUS (CMV) - PUSPAWATI, N. M.; ARI MAYADEWI, N.N. (AGRITROP, 2010)
Mosaic disease outbreaks on chili (Capsicum annum) associated with Cucumber Mosaic Virus (CMV) is serious worldwide. The use of resistant cultivars is an effective control to reduce the loss of yield caused by virus’s infections. The objective of this study is to detect the resistant characters of CMV in chili using OPH-17 and OPA-20 RAPD primers. The inoculation of CMV in PSPT-C11, C17-PSPT, ICPN 7 # 3 and 1 Chilibangi 1 varieties cause systemic mosaic symptoms vary from mild mosaic to the mosaics with malformations. PSPT-C11 varietiy showed rather resistant, while the varieties PSPT-C17 and Chilibangi 1 are susceptible, and ICPN 7 # 3 is very susceptible. OPH-17 and OPA-20 primers could not be used to determine the resistance differences against CMV in PSPT-C11, C17-PSPT, ICPN 7 # 3 and Chilibangi 1 varieties.